2016
DOI: 10.1245/s10434-016-5241-0
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet and Anticoagulant Medications Significantly Increase the Risk of Postoperative Hematoma: Review of over 4500 Thyroid and Parathyroid Procedures

Abstract: Purpose Antiplatelet and/or anticoagulant medication use is common. Abstinence a week before surgery may still result in altered hemostasis. The study aim was to report on perioperative antiplatelet and anticoagulant use in thyroidectomy and parathyroidectomy patients, and to determine the association with postoperative hematoma (POH) rates. Methods Retrospective review of a prospective endocrine surgery database was performed. Procedure extent was defined as unilateral, bilateral, or extensive. Antiplatelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 37 publications
1
30
0
1
Order By: Relevance
“…Complications after thyroidectomy are wellknown, but are rare; these include recurrent laryngeal nerve paralysis, hypoparathyroidism, and post-thyroidectomy hematoma. [1][2][3][4][5][6][7][8][9][10][11] In this study, we sought to identify perioperative risk factors for PH, with emphasis on perioperative hemodynamics and medications, along with well-known risk factors, such as sex, age, and type of operation. 2 Notably, PH is an uncommon, but life-threatening complication, which can induce upper airway obstruction, acute respiratory failure, and death.…”
Section: Introductionmentioning
confidence: 99%
“…Complications after thyroidectomy are wellknown, but are rare; these include recurrent laryngeal nerve paralysis, hypoparathyroidism, and post-thyroidectomy hematoma. [1][2][3][4][5][6][7][8][9][10][11] In this study, we sought to identify perioperative risk factors for PH, with emphasis on perioperative hemodynamics and medications, along with well-known risk factors, such as sex, age, and type of operation. 2 Notably, PH is an uncommon, but life-threatening complication, which can induce upper airway obstruction, acute respiratory failure, and death.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to severe or permanent hypocalcemia as recently discussed, hematoma, recurrent laryngeal nerve injuries, and permanent hypoparathyroidism are among the more grave complications. Postoperative hemorrhage or hematoma is exceedingly rare in parathyroidectomies, with a reported rate as low as 0.1% . Injury to the recurrent laryngeal nerve are often addressed but most typically in the form of transient neuropraxia.…”
Section: Introductionmentioning
confidence: 99%
“…Although a relatively uncommon complication, if not promptly recognized and managed, a neck hematoma can be fatal. Thyroidectomy has a higher risk of postoperative bleeding than parathyroidectomy, and bilateral procedures also confer a higher risk of bleeding than unilateral procedures . Other risk factors for bleeding include older age, male sex, Graves' disease, prior thyroid surgery, and neck dissection …”
Section: Assessment Of Bleeding Risk – Common Head and Neck Proceduresmentioning
confidence: 99%
“…One retrospective analysis of 2514 patients undergoing thyroidectomy or parathyroidectomy found that postoperative hematoma rates were higher in patients receiving 325 mg of aspirin (0.8%), clopidogrel (2.2%), oral anticoagulants, such as warfarin or dabigatran (2.2%), and injectable anticoagulants, such as enoxaparin and heparin (10.7%) compared with patients not receiving antithrombotics (0.5%) or those receiving <325 mg of aspirin (0.1%). This study included patients taking antithrombotic medications within 2 weeks of surgery, including those who stopped the medications 5‐7 days before surgery . A meta‐analysis of bleeding after thyroidectomy included 6 studies with patients taking antithrombotic medications and found a nearly 2‐fold increased risk of postoperative hemorrhage (2.48% compared to the overall rate of 1.34%) .…”
Section: Assessment Of Bleeding Risk – Common Head and Neck Proceduresmentioning
confidence: 99%
See 1 more Smart Citation